Industry of Ukraine: characteristics, trends and problems of development - Moroz, Oleg (Management and Entrepreneurship: Trends of Development, 2019)
New transformation processes occurring in the socio-political life of Ukraine encourage new requirements for the development of the national economy in general and its individual components in particular. In this connection, the state and development trends of industry, as one of the leading and main sectors of the country's economy, ensures its sustainable and progressive development, as well as the country's proper place in the international division of labor, acquire one of the highest priorities for achieving the strategic development goals of Ukraine in whole and their research is important and relevant.The purpose of the article is to characterize the current situation in Ukraine’s industry, to highlight trends and problems of its development and to develop proposals for possible ways of leveling the negative impact of these problems on the economy.Research limitations/implications. The paper presents the characteristics of the existing functional and sectoral structure of the industry of Ukraine and its intersectoral industrial production complexes.Findings. The analysis of existing trends in the development of industrial production, covering the entire period of independence of Ukraine, revealed a number of problems. At the same time, the emergence of problems in the development of industry in Ukraine was traced both from the rupture of economic ties caused by the “parade of sovereignties” and the “collapse of the USSR”, and under the influence of global economic crises (1997 and 2008), as well as events related associated with the annexation of parts of the territory of the country, partial occupation and war in the east of the country (2014). The article highlights both the peculiarities and problematic aspects of the modern development of the industrial sector of the economy of Ukraine, as well as the presence of certain competitive advantages of the domestic industry.Originality/value. The ways for further research of the problem and development of the concept (program) of industrial development in the interests of the country's economy and society as a whole are proposed. This concept (program) involves the creation of the necessary conditions for the overwhelming majority of the owners of industrial groups of influence in its implementation, as well as their responsibility for taking and fulfilling certain obligations proposed by the state (in particular, among other proposed in the article) obligations. As a basis for the development of this concept (program), it was proposed to conduct a comprehensive study of the best practices of the functioning of industry, and a balanced definition of the basic principles for selecting reference countries to study their practical experience of “neoindustrialization”, taking into account national institutional features, existing limitations and problems and also competitive advantages of industrial enterprises of Ukraine.